Pelatihan Media Pembelajaran Berbasis Virtual/Digital sebagai Peningkatan Kompetensi Dosen - Ummul Hasanah; Muh. Rapi; Syahriani; Suhardiman; Andi Tenri Ola Rivai; Ayyub Ibrahim (KHIDMAH: Jurnal Pengabdian Masyarakat, 2022)
Training on the use of digital-based learning media aims to provide additional competence to lecturers in making new technology-based media. Subject service is a lecturer at the Faculty of Tarbiyah and Teacher Training UIN Alauddin Makassar as many as 12 participants with representatives from several study programs in the Faculty of Tarbiyah and Teacher Training UIN Alauddin. The data collection instrument uses a questionnaire that is distributed through a google form. As many as 75% of participants felt that this training was "very appropriate" and 25% "fit" the needs of the participants. In terms of material coverage, 58.3% of participants chose the "very covering" category and another 41.7% in the "covers" category. Trainees have an understanding of the "very understanding" and "understanding" categories as well as the usefulness of the training material with 83.3% "very useful" and 16.7% in the category of "useful". The results of the survey showed the high needs and how far the applications obtained by the trainees in improving their competence as lecturers. This training is expected to be able to become a reference for lecturers in producing outputs in the form of more up-to-date learning media so as to improve learning.